Effects Teacher Certification and Teacher Commitment on Teacher Performance - Rosadiro Cahyono3, Musthafa1 Kuswandi 2 (International Journal of Scientific Research and Management (IJSRM), 2017)
Purpose - The purpose of this study was to analyze the effect of teacher certification and teachercommitment to teacher performance.Design / Methodology / Approach - The analysis technique in this study is using Structural EquationModeling (SEM) with AMOS 18 program. Sampling is using random sampling, to the e-commerceusers. Some 450 respondents took part and the size of the sample that can be used is 180 after theselection process.Findings and implications - First: stated that the certification of teachers significantly influence theperformance of teachers is received. Second: stated that the certification of teachers significantlyinfluence the performance of Limitations - Although the justification for using sample based on ethnic and regional divisions in thecountry of Indonesia for research related to teacher certification is already exist in the literature, thissample may not reflect the actual total teacher population in the world